Knitting by nature : 19 patterns for scarves, wraps, and more - Thies, Sheryl, 1951- (Martingale, 2012)
In this follow-up to her wildly popular books "Ocean Breezes" and "Nature's Wrapture", Sheryl Thies has outdone herself wit a stunning new collection of nature-inspired designs. Revel in knitting ideas gathered from a wide array of flowers, grasses, and vines.--Back Cover